Pengaruh Penerapan Gaya Mengajar Self Check Style Terhadap Hasil Belajar Gerak Dasar Pada Menendang Bola Dengan Punggung Kaki Dalam Permainan Sepak Bola Pada Peserta Didik Kelas XI SMK Negeri 1 Tomohon - Stive Karundeng; Yuliana Sattu; Djhoni Alfrits Sunkudon (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Physical education is something that cannot be separated from education in general because physical education fulfills all the goals and functions of education through the development of three aspects, namely cognitive, affective, and psychomotor of the students. Based on observations by the researcher, particularly in the 11th grade, many students still lack understanding and ability in demonstrating the basic movement of kicking a ball with the back of the foot in soccer. The hypothesis in this research is "The Self Check Style teaching method has an influence on improving the basic movement learning outcomes of kicking a ball with the back of the foot in soccer among the 11th-grade students of SMK Negeri 1 Tomohon.". The operational objective of this research is to compare whether the average score of basic movement learning in kicking with the back of the foot among students who are given treatment with the Self Check Style teaching method is higher than the average score of basic movement learning in kicking with the back of the foot in football among students who are not given the Self Check Style teaching method. This research uses the experimental method. The population consists of 194 students from the XI grade of SMK NEGERI 1 TOMOHON. And the sample consists of 40 students. The instrument of this research is a basic movement ability test for kicking with the back of the foot in soccer. The result of the hypothesis testing obtained a t-value of 9.2857. Based on the t-distribution table at ∝0.05 with degrees of freedom n1+n2-2 = 20+20-2= 38, the t-table value is obtained as 2.024. so the calculated t is greater than the table t (calculated t > table t). Based on the testing criteria, if the calculated t-value is greater than the table t-value, then the null hypothesis (HO) is rejected and the alternative hypothesis (HA) is accepted. The conclusion of this study is that the Self Check style of teaching has a significant impact on the improvement of basic movement learning in kicking a ball with the back of the foot in soccer among the 11th-grade students of SMK NEGERI 1 TOMOHON.